2023
DOI: 10.1021/acs.est.2c08974
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Bioaccumulation and Cortisol Interact to Influence Endocrine and Immune Biomarkers in a Free-Ranging Marine Mammal

Abstract: Mercury bioaccumulation from deep-ocean prey and the extreme life history strategies of adult female northern elephant seals (Mirounga angustirostris) provide a unique system to assess the interactive effects of mercury and stress on animal health by quantifying blood biomarkers in relation to mercury (skeletal muscle and blood mercury) and cortisol concentrations. The thyroid hormone thyroxine (tT4) and the antibody immunoglobulin E (IgE) were associated with mercury and cortisol concentrations interactively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The mean concentrations of testosterone, T3, T4, and cortisol were 1.4 ± 2.7, 51.9 ± 48.4, 10.6 ± 5.4, and 23.0 ± 31.8 ng/g lw, respectively (Table S10). As a stress indicator in mammals, cortisol tends to positively correlate with the severity of the stressor . In this study, no significant correlations were found between the concentrations of all five OPE congeners (TDBPP, TBOEP, TCIPP, TCrP, and TDCIPP) and cortisol in humpback dolphins (Figure S4), suggesting that current OPE exposure did not cause physiological stress in the dolphin species.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The mean concentrations of testosterone, T3, T4, and cortisol were 1.4 ± 2.7, 51.9 ± 48.4, 10.6 ± 5.4, and 23.0 ± 31.8 ng/g lw, respectively (Table S10). As a stress indicator in mammals, cortisol tends to positively correlate with the severity of the stressor . In this study, no significant correlations were found between the concentrations of all five OPE congeners (TDBPP, TBOEP, TCIPP, TCrP, and TDCIPP) and cortisol in humpback dolphins (Figure S4), suggesting that current OPE exposure did not cause physiological stress in the dolphin species.…”
Section: Resultsmentioning
confidence: 54%
“…The findings suggest that OPE exposure may have impacted the thyroid function in the dolphins. While studies on the relationship between OPEs and thyroid hormones in cetaceans are limited, in vitro and in vivo studies have demonstrated that OPE exposure could cause thyroid hormone disturbances in mammals, leading to an increased risk of cancer, impaired brain development of offspring during gestation, and other adverse health outcomes. , Considering the sensitive thyroid axis of marine mammals, which helps manage the different demands of their lifestyles, our findings suggest that disturbances in thyroid hormones might have adverse downstream health effects to humpback dolphins . For example, increased oxygen consumption has been documented in diving harbor seals (Phoca vitulina) with induced hyperthyroidism …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation